Adeno-associated virus (AAV)-3-based vectors transduce haematopoietic cells not susceptible to transduction with AAV-2-based vectors - Handa, A; Muramatsu, S; Qiu, J; Mizukami, H; Brown, K (2000)
Although adeno-associated virus (AAV)-2 has a broad tissue-host range and can transduce a wide variety of tissue type, some cells, such as erythro-megakaryoblastoid cells, are non-permissive and appear to lack the AAV-2 receptor. However, limited studies have been reported with the related dependovirus AAV-3. We have previously cloned this virus, characterized its genome and produced an infectious clone. In this study, the gene for green fluorescent protein (GFP) was inserted into AAV-2- and AAV-3-based plasmids and recombinant viruses were produced. These viruses were then used to transduce haematopoietic cells and the transduction efficiencies were compared. In contrast to recombinant (r) AAV-2, rAAV-3 successfully transduced erythroid and megakaryoblastoid cells, although rAAV-2 was superior in transduction of lymphocyte-derived cell lines. Recently, it was reported that heparan sulphate can act as a receptor of AAV-2. The infectivity of rAAV-2 and rAAV-3 was tested with mutant cell lines of Chinese hamster ovary cells that were defective for heparin or heparan sulphate expression on the cell surface. There was no correlation between the ability of rAAV-2 or rAAV-3 to infect cells and the cell surface expression of heparan sulphate and, although heparin blocked both rAAV-2 and rAAV-3 transduction, the ID50 of rAAV-3 was higher than that of rAAV-2. In addition, virus-binding overlay assays indicated that AAV-2 and AAV-3 bound different membrane proteins. These results suggest not only that there are different cellular receptors for AAV-2 and AAV-3, but that rAAV-3 vectors may be preferred for transduction of some haematopoietic cell types.